1997
DOI: 10.1097/00005131-199704000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary Nailing of Unstable Diaphyseal Fractures of the Tibia with Distal Intraarticular Involvement

Abstract: The indications for intramedullary nailing of unstable diaphyseal tibia fractures may be extended to include certain fractures with distal extension into the ankle joint, as well in a tibial shaft fracture occurring in combination with a noncontiguous ipsilateral ankle fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
0
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 19 publications
4
57
0
4
Order By: Relevance
“…Nonunion occurred in 8 % of the fractures in this study. This compares favourably to the reports by Im and Tae [6] and Vallier et al [32] nailing groups, whereby the rate of delayed and non-union after nailing distal tibial fractures vary between 0 and 23 % in the literature [3,6,8,13,14,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Screw failure remains a common problem with small diameter nails [2,15,16].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Nonunion occurred in 8 % of the fractures in this study. This compares favourably to the reports by Im and Tae [6] and Vallier et al [32] nailing groups, whereby the rate of delayed and non-union after nailing distal tibial fractures vary between 0 and 23 % in the literature [3,6,8,13,14,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Screw failure remains a common problem with small diameter nails [2,15,16].…”
Section: Discussionsupporting
confidence: 74%
“…On the other hand, a study by the AO centre in Davos analysing tibial fractures in Swiss clinics from 1994 to 1997 showed delayed union in 17 out of 94 cases treated by unreamed nailing that had revision surgery, from which ten were simple distal fractures without severe soft tissue damage or complicating factors [18]. Other authors reported good union with reamed nails in distal tibial fractures despite the technically demanding procedure [13,14,22,24,[27][28][29][30][31][32]. In a multicentre European study, Attal et al reported on 91 distal third tibial fractures treated with the Expert tibial nail (ETN®).…”
Section: Discussionmentioning
confidence: 99%
“…Nonoperative management has been recommended for treatment of spiral tibial shaft fractures and associated ankle fractures [7,17]. The current treatment recommendations are predominantly operative [4,10,13,14]. This makes preoperative diagnosis of the associated posterior malleolus fracture imperative.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our experience and that of others, however, the potential for late displacement of the posterior malleolus warrants early detection and stabilization of these injuries. In a study which reported on open and closed diaphyseal fractures with distal intraarticular fracture extension and displacement less than 5 mm, the authors recommend limited open reduction and internal fixation or percutaneous lag screw fixation of the articular component followed by intramedullary nailing [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation